Strains of Rodents and the Pharmacology of Learning and Memory - Martine Ammassari-Teule; Claudio Castellano (Neural Plasticity)
Mendelian genetic tools have extensively been used to improve the description of the pharmacological mechanisms involved in learning and memory. The first part of this short review describes experiments involving the bidirectional selection of rats or mice for extreme behavioral characteristics or for sensitivity to pharmacological treatments. The second part focuses specifically on inbreeding. In conclusion, the advantages and the limits of a Mendelian pharmacogenetic approach of learning and memory are discussed.